Brunswickgrass or Paspalum nicorae: A Weed Contaminant in Southern Pastures and Bahiagrass Seed Production Fields - Ann R. Soffes Blount; Marcelo Osorio Wallau; Brent A. Sellers; Dennis Hancock; Leanne Dillard; Jose C. B. Dubeux; Cheryl L. Mackowiak; Joao Mauricio Buen Vendramini; Clay T. Cooper (EDIS)
Brunswickgrass (Paspalum nicorae Parodi) is becoming a problematic weed in summer perennial grass pastures in the Southeast. The plant is competitive with bahiagrass and bermudagrass. Since it is less palatable, it can eventually dominate a perennial grass pasture. Brunswickgrass has become naturalized and has reportedly contaminated bahiagrass seed fields and pastures in the southeastern states, including some of the important counties for seed production in Florida, such as Gilchrist, Levy, Alachua, Citrus, and Sumter. This 4-page fact sheet provides an overview of brunswickgrass and discusses its appearance, variety/germplasm, and management. Written by Ann Blount, Marcelo Wallau, Brent Sellers, Dennis Hancock, Jose Dubeux, Cheryl Mackowiak, Joao Vendramini, and Clay Cooper, and published by the UF/IFAS Agronomy Department, April 2018. http://edis.ifas.ufl.edu/ag408